Stress level among parents in Klang Valley during covid-19 outbreak and its contributing factors - Shamhari, Asma' 'Afifah; Mohd Saat, Nur Zakiah; Ab. Manam, Farah Fatin; Hanipah, Jamilah; Mohd Zain, Mardhiah; Md Ghazi, Md Gezani; Md Saironi, Nurul Afiqah; Mohd Saat, Nur Ashikin; Nahendran, Prasanthini; Ariffin, Shazrina; Magallanes, Shereen Song (GADING Journal for the Social Sciences, 2023)
The COVID-19 outbreak has affected the health, physical, social, mental and economy of people around the globe. Currently, Movement Control Order (MCO), often referred to as partial lockdown, signifies a major step taken by the government to contain the Covid-19 pandemic in Malaysia. Thus, this study was conducted to investigate COVID-19 outbreak impact factors that contribute to higher stress level among parents in Klang Valley resulting from the MCO. This crosssectional study was designed with the sample size of 126 through a convenience sampling method. Parents with at least one child below 12 years old were recruited to answer an online questionnaire that consists of Coronavirus Impact Questionnaire (CIQ) and Perceived Stress Scale (PSS). The result showed a positive correlation between impact COVID-19 and stress level among parents in Klang Valley with Pearson Correlation of r (123)=0.56, p<0.01. The study revealed that, COVID-19 pandemic was moderately impactful to parents with 62% in agreement that the situation had affected them psychologically. From the recruited population, 73% of the parents reported to have experienced moderate to high stress levels. Thus, the MCO shows a significant association between the level of stress among parents and the COVID-19 pandemic. The findings offer insights into the elements that affect parents' stress levels during the COVID-19 pandemic and recommendations for policymakers on how to lessen this burden, particularly for nuclear families.